"Institutional Dimensions of e-Government Development: Implementing the Business Reference Model in the United States and Korea". (September 2013) - Eom, Seok-Jin
Why do similar e-government initiatives, implemented by different nations but aimed at achieving similar policy goals, produce different outcomes? To answer this question, this study examines institutional arrangements for e-government development during the Bush administration in the United States and the Roh Moo-hyun administration in Korea. The results of this study demonstrate how different institutional arrangements for e-government developments in terms of the concentration of authority based on differing legal frameworks and the development of diverse and powerful managerial tools for control and coordination contributed to producing different outcomes with regard to building Business Reference Models (BRM) in the two nations.